Implementation Of Arabic Language Learning Strategy In Improving The Quality Of Graduates In Nurul Private Tsanawiyah Madrasah Islam, Kuala District, Langkat Regency - Syamsu Nahar; Zulheddi Zulheddi; Zulhafnita Zulhafnita; M Fajri Syahroni Siregar (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2021)
This research is qualitative research with descriptive methods. Data analysis techniques use qualitative data analysis techniques by analyzing 3 data, namely data reduction, data presentation, and conclusion drawing. The results showed that the strategy used in Arabic learning is learning with mufrodat and supported by other strategies, like grammar and listening. The implementation of Arabic language learning in Madrasah Tsanawiyah Nurul Islam District Kuala Langkat district is considered inadequate or still use the old method so that there is no improvement in the learning method. Simultaneously, the obstacle faced is students' difficulty following Arabic language learning because it only memorizes mufrodat so that it disappears faster memorization.